A programmable pseudo negative stiffness control device and its role in stay cable vibration control. (1st July 2022) - Xu, Yan-Wei; Xu, Zhao-Dong; Guo, Ying-Qing; Zhou, Min; Zhao, Yu-Liang; Yang, Yang; Dai, Jun; Zhang, Jie; Zhu, Chen; Ji, Bo-Hai; Du, Yan-Liang; Chen, Zheng-Qing
Highlights: The proposed MR based pseudo negative stiffness control approach is one of the most practical and efficiency semi-active vibration control for stay cable. Clarify the gain role of pseudo-negative stiffness force in stay cable vibration control in the theoretical asymptotic solution. Establish a real-time simulation model of the stay cable coupled with time-varying control system. Abstract: Stay cables are prone to large amplitude vibrations, due to their low inherent damping and high lateral flexibility. In this study, one magnetorheological (MR) damper based programmable intelligent control device is developed to control the vibration of the stay cable more practically and efficiently. The proposed programmable scheme possesses the advantages of low energy consumption, less real time calculation and dynamic input. Its control oriented dynamic model integrated with programmable pseudo negative stiffness (PNS) strategy is built. And its beneficial role in the vibration control is explained in the complex eigenvalue theory analysis of stay cable with MR damper based programmable PNS force. Finally, the simulation of dynamic response of stay cable shows the superiority of programmable control scheme. Its realization demonstrates the feasibility of the single-input programmable PNS scheme experimentally. The dynamic response simulation of stay cable shows that MR damper based PNS scheme can offer better damping performance than conventional control method and its additional damping ratio is 1.63 times higher than that of optimal MR damper passive-on control.